Case Report and Literature Review: Behçet’s Disease With a Novel TFPI Gene Mutation - Ma, Jiewen; Sun, Wengang; Tang, Liang; Yang, Di (Frontiers in Medicine, 2022)
We report a case of Behçet's disease (BD) with a newly identified tissue factor pathway inhibitor (TFPI) gene mutation. The patient suffered from recurrent deep vein thrombosis and dual sinus thrombosis which could not be relieved by constant anticoagulation therapy. Slight relapsing oral lesion was the initial manifestation of BD but was neglected. Genital ulcers and ocular symptoms were manifest eight-month later than vascular involvement. The patient was diagnosed with BD at last and a novel mutation in TFPI was identified simultaneously. After administration with azathioprine and dexamethasone, the clinical symptoms were quickly gone and no relapse was found during seven-month follow-up.